Students’ heterogeneous mathematical critical thinking skills in problem-based learning: A meta-analysis investigating the involvement of school geographical location - Suparman, Suparman; Juandi, Dadang; Martadiputra, Bambang Avip Priatna (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
A discrepancy exists in students' mathematical critical thinking skills (MCTS) in mathematics classrooms implementing problem-based learning (PBL). The factor of school geographical location is predicted to affect the skill distinction of the students. This study aims to investigate and examine the school's geographical location assumed as a moderating factor of students' heterogeneous MCTS in PBL. Meta-analysis of 58 relevant documents containing 3,946 students and generating 59 effect sizes in the Hedges g unit was performed to conduct this study. Searching and selecting literature found 58 documents published from 2011 to 2021, consisting of 40 journal articles and 18 conference papers. Some tests, such as Q Cochrane and Z, were applied to analyze the data. The results showed that the school's geographical location was not a significant moderating factor that affected students' heterogeneous MCTS in PBL. In addition, PBL intervention significantly positively affected metropolitan, urban, and rural students' MCTS. Still, PBL intervention was more effective in the metropolitan area in enhancing students' MCTS than in urban or rural areas. This study suggests Indonesian government conduct the equable distribution of competent teachers and complete the facility and infrastructure of schools in each geographical location.